Health impact assessments in hospital community benefit: A multiple case study of the use of HIAs at Children's Hospital Colorado - Gregory Jackson Tung; Venice Ng Williams (Indiana University-Purdue University Indianapolis, 2017)
Objective:  To explore the use of Health Impact Assessments (HIAs) within non-profit hospital community benefit activities. Methods:  We constructed case studies of three HIAs that were conducted in collaboration with Children's Hospital Colorado as part of the hospital's community benefit portfolio. These HIAs were part of a pilot that was funded by the Health Impact Project, a collaboration of the Robert Wood Johnson Foundation and The Pew Charitable Trusts. Results:  HIAs provided Children's Hospital Colorado with a transparent and systematic process for generating evidence-based recommendations with community and stakeholder feedback within the hospital's community benefit activities. HIAs were used to generate recommendations to inform community benefit planning activities and to generate public policy recommendations to enhance child health. The case studies highlighted several issues that need to be addressed in order to further advance the use of HIA within hospital community benefit activities including: use of HIA on explicit health issues, hospital capacity for HIA, potentially broadening the scope of HIA recommendations, and the use of HIA to generate recommendations from broad priority areas. Conclusion: HIAs can help meet the need for established, evidence-based, and stakeholder responsive tools and processes to be used within non-profit hospital community benefit activities. In meeting this need, the non-profit hospital community benefit area can potentially serve as a major institutional home for the practice of HIA. There is a need for additional research and practice innovation to further explore and refine the use of HIA within non-profit hospital community benefit activities.